Chest X-ray Sizing for Lung Transplants Reflects Pulmonary Diagnosis and Body Composition and Is Associated With Primary Graft Dysfunction Risk. Issue 2 (February 2021) - Li, David; Weinkauf, Justin; Hirji, Alim; Nagendran, Jayan; Kapasi, Ali; Lien, Dale; Halloran, Kieran
Abstract : Background: Donor-recipient oversizing based on predicted total lung capacity (pTLC) is associated with a reduced risk of primary graft dysfunction (PGD) following lung transplant but the effect varies with the recipient's diagnosis. Chest x-ray (CXR) measurements to estimate actual total lung capacity (TLC) could account for disease-related lung volume changes, but their role in size matching is unknown. Methods: We reviewed adult double lung transplant recipients 2007–2016 and measured apex-to-costophrenic-angle distance (=lung height) on pretransplant donor and recipient CXRs (oversized donor-recipient ratio >1; undersized ⩽1]. We tested the relationship between recipient lung height to actual TLC; between lung height ratio and donor/recipient characteristics; and between both lung height ratio or pTLC ratio and grade 3 PGD with logistic regression. Results: Two hundred six patients were included and 32 (16%) developed grade 3 PGD at 48 or 72 hours. Recipient lung height was related to TLC ( r 2 =0.7297). Pulmonary diagnosis, donor BMI, and recipient BMI were the major determinants of lung height ratio (AUC 0.9036). Lung height ratio oversizing was associated with increased risk of grade 3 PGD (odds ratio, 2.51; 95% confidence interval, 1.17-5.47; P = 0.0182) in this cohort, while pTLC ratio oversizing was not. Conclusions: CXR lung height estimates actual TLC and reflects pulmonary diagnosis and body composition. Oversizing via CXR lung height ratio increased PGD risk moreso than pTLC-based oversizing in our cohort. Abstract : Supplemental Digital Content is available in the text.